Loss of Sprouty2 in human high‐grade serous ovarian carcinomas promotes EGF‐induced E‐cadherin down‐regulation and cell invasion. Issue 3 (20th December 2014) - So, Wai-Kin; Cheng, Jung-Chien; Fan, Qianlan; Wong, Alice S.T.; Huntsman, David G.; Gilks, C. Blake; Leung, Peter C.K.
Abstract : Sprouty (SPRY) proteins are well‐characterized factors that inhibit receptor tyrosine kinase signaling. Our Human Exonic Evidence‐Based Oligonucleotide (HEEBO) microarray results showed that the mRNA levels of SPRY2, but not of SPRY1 or SPRY4, are down‐regulated in high‐grade serous ovarian carcinoma (HGSC) tissues and epithelial ovarian cancer (EOC) cell lines. Molecular inversion probe (MIP) copy number analysis showed the deletion of the SPRY2 locus in HGSC. Overexpression of SPRY2 reduced EGF‐induced cell invasion by attenuating EGF‐induced E‐cadherin down‐regulation. Moreover, a positive correlation between SPRY2 and E‐cadherin protein levels was observed in HGSC tissues. This study reveals the loss of SPRY2 in HGSC and indicates an important tumor‐suppressive role for SPRY2 in mediating the stimulatory effect of EGF on human EOC progression. Abstract : SPRY2 is down‐regulated in high‐grade serous ovarian carcinomas. SPRY2 gene is deleted in high‐grade serous ovarian carcinomas. Overexpression of SPRY2 attenuates EGF‐induced down‐regulation of E‐cadherin. Overexpression of SPRY2 attenuates EGF‐induced cell invasion.